Clinical Significance of Somatostatin Receptor (SSTR) 2 in Meningioma - Wu, Wei; Zhou, Yunxiang; Wang, Yali; Liu, Lihong; Lou, Jianyao; Deng, Yongchuan; Zhao, Peng; Shao, Anwen (Frontiers in Oncology, 2020)
Somatostatin receptor (SSTR) 2, widely expressed in meningioma, is a G-protein-coupled receptor and can be activated by somatostatin or its synthetic analogs. SSTR2 is therefore extensively studied as a marker and target for the diagnosis and treatment of meningioma. Accumulating studies have revealed the crucial clinical significance of SSTR2 in meningioma. Summarizing the progress of these studies is urgently needed as it may not only provide novel and better management for patients with meningioma but also indicate the direction of future research. Pertinent literature is reviewed to summarize the recent collective knowledge and understanding of SSTR2’s clinical significance in meningioma in this review. SSTR2 offers novel ideas and approaches in the diagnosis, treatment, and prognostic prediction for meningioma, but more and further studies are required.